“DISCERNING THE SPIRIT (S)” DALAM KUASA POLITIK: SEBUAH PERSPEKTIF TEOLOGI PENTAKOSTAL - Minggus Minarto Pranoto (Sekolah Tinggi Theologia Abdiel, 2019)
Pentecostal theology considers toward the reality of political power from pneumatological perspective. Political theology of Pentacostal asserts that such a reality is also the problem of spiritual ethic. It is a mistake if such a reality can be analysised from the methodological approach of academic socialonly. To achieve the aim of this writing, the writer will use the theological thinking of Amos Yong who emphasizes that the demonic reality can not be understood if it does not embody into a concrete form. Yong’s theology will be related to the theory of Daniel Day William who says that the manifestations of the demonic modes can be explained through the destructive impacts seen in human’s life. The writer also tries to give critical reflection of political power from Pentacostal theology.